Diabetes in Israel- do all patients receive equal care?. (13th November 2019) - Wolff Sagy, Y; Krieger, M; Horwitz, E; Ben-Yehuda, A; Paltiel, O; Ravel-Vilk, S; Manor, O; Calderon-Margalit, R
Abstract: Background: Diabetes Mellitus (DM) is associated with micro- and macro-vascular complications, leading to high burden of morbidity and mortality. Populations of low socioeconomic position (SEP) in various countries were found to have increased prevalence of the disease, worse glycemic control, and increased complications. We aimed to examine whether there are social disparities in diabetes care in Israel, as reflected in a national program for quality indicators. Methods: The Israel National Program for Quality Indicators in Community Healthcare obtains data from electronic medical records from all health plans, covering the entire Israeli population. In 2017, 497, 397 individuals aged >18 years were identified with DM. DM prevalence, quality of care indicators, including process and intermediate outcomes were explored by SEP categories (1-10), determined according to residential addresses. Results: DM prevalence in Israeli adults in 2017 was 9.7%, showing a strong SEP gradient, with higher prevalence in individuals of lower SEP. No SEP disparities were observed in process indicators with overall rates of documentation of hemoglobin A1c (HbA1c) of 90.9%, ophthalmologic examinations of 72.5%, and kidney function examinations of 92.5%. However, strong SEP disparities were observed in the prevalence of uncontrolled diabetes (HbA1c≥9%), with an overall rate of 10.0%, and a 5.4-times higher rate in diabetics of the lowest SES level (23.5%) compared with the highest SEP level (4.3%). A somewhat weaker gradient was seen for the well-control of DM (HbA1c<7-8%, according to duration of disease and age), with an overall rate of 69.7%, and a 1.7 ratio, comparing diabetics of the highest vs the lowest SEP level. Conclusions: These findings suggest that access to care does not explain SEP disparities in diabetes control in Israel. There is a need to explore the underlying social, cultural, and possibly the benefits-policy determinants of poor control among individuals of low SEP. Key messages: Wide socioeconomic disparities are present among Israeli adults in diabetes mellitus prevalence and control rates, but not in care processes indicators. These findings call for a deeper understanding of the determinants and perhaps a revision of current social benefits policy, which may encourage lack of glycemic control.